Influence of end-effect and end-winding on the electromagnetic losses and efficiency in high speed permanent magnet machines - Ahlam Luaibi Shuraiji; Sabah A. Gitaffa; Kassim Rasheed Hameed; Salam Waley Shneen (Institute of Advanced Engineering and Science, 2022)
Permanent-magnet excitation machines (SPMMs) having mounted magnet on the outer surface of their rotor are preferred for high speed applications such as turbochargers, mechanical turbo-compounding systems, racing engines and fuel pumps, over other types of machines including induction and switched-reluctance machines, since the SPMMs integrate the features of high torque density, compact rotor structure, high reliability and simple structure. However, in the SPMMs, due to the need for a retaining sleeve for the rotor, a large magnetic airgap results and consequently a large magnet thickness is required, hence the magnetic end-effect is relatively high. On the other hand, the use of an overlapping distributed winding leads to a significantly large end-winding length. Hence, the end-effect and the end-winding influences on the performances of a high-speed SPMM is considered in this paper. With a view to get the impact of the end-effect, a comparison between three-dimensional (3D-FEA) results and counterparts two-dimensional finite element analyses (2D-FEA) have been conducted. Results show that, higher efficiency at low torque and low speed due to the low electromagnetic losses and at high speeds due to the high flux-weakening capability are seen when the influences of end-effect as well as end-winding are taken into account.